ON THE ISSUE OF VERIFICATION OF THE EFFECTIVENESS OF THE INTERDISCIPLINARY APPROACH APPLICATION OF IN TRAINING MASTERS OF PUBLIC HEALTH - Natalia M. Kalyniuk; Lubov M. Romaniuk; Nina Ye. Romaniuk (Alfred Nobel University Publisher, 2021)
The expediency of conducting research and experimental work at the stage of identifying opportunities to improve the educational process in training future public health professionals on the basis of interdisciplinary integration is substantiated. The article is devoted to the role of experimental pedagogical research as a means of testing the effectiveness of interdisciplinary integration in the training of future public health professionals. It is generalized that the issue of professional training of future specialists in the specialty «Public Health» in the pedagogical literature is considered as a component of professional self-determination and professional development in the context of the study of professional self-awareness. It is proved that the interdisciplinary integration in the training of future public health professionals is an integrated component that combines individual and personal features (awareness of the choice of profession, completeness and strength of knowledge in the chosen profession, the formation of professionally significant and empathetic qualities). It is socially oriented and oriented at building relationships and positioning oneself in the team, develops the ability to make decisions independently and take responsibility as well as personality characteristics; it implies the presence of strong beliefs in the values of the profession of public health specialist for the design of their own subjective deontological position in the work connected with their specialty. It is substantiated that the professional training of future medical professionals on the basis of interdisciplinary integration involves creating conditions for identifying personal and social experience of students with the profession and the professional community, is a process of mastering normative professional requirements that allow them to adequately perceive medical reality, as well as to develop professionally expedient strategies and tactics, tasks and plans of professional activity, to consciously regulate one's own behavior within the established professional and normative imperatives. It was found that the professional training of future public health professionals on the basis of interdisciplinary integration is characterized by the presence of future professionals with a set of knowledge that reflects the substantive essence of intellectual, ideological and moral values; the ability to predict and design the process of professional activity taking into account its specifics in interaction with colleagues and patients and is determined by the content of professional medical ethics and deontology, ethical and moral imperatives and professional and ethical ideals and values of public health. The peculiarities of the formation of professional training of future public health specialists on the basis of interdisciplinary integration are studied.